Profil genetika DNA mikrosatelit kromosom-Y masyarakat laki-laki soroh Kayuan Pasek Catur Sanak Bali Mula - I Ketut Junitha; Ni Luh Watiniasih; Ni Luh Putu Ria Puspitha (Universitas Udayana, 2017)
This research is conducted to find out the genetic profiles of Kayuan clan which is belong to Pasek Catur Sanak Bali Mula, indigenous Balinese people. The DNA profiles is identified by using Microsatellite DNA of Y chromosome. Genes or DNA in Y chromosome are descended from father to son (patrilinealism). Four loci of microsatellite DNA from Y chromosome are used, including DYS19, DYS390, DYS393 and DYS395 to amplified DNA samples from 67 males probands. The probands are people of Kayuan clan from Siakin, Songan, Blandingan and Kutuh villages, Kintamani sub district and others are originally from Jehem village, Tembuku sub district, Bangli regency. The research found 12 allele varieties from all the analyzed loci, which resulted in low genetic diversity (0.33 + 0.001). There are 4 combinations alleles of 4 loci that created12 various haplotypes, the greatest one is haplotype 1 (0.39), followed by haplotype 2 (0.16), haplotype 7 (0,12) and the smallest one is haplotype 6 (0,10). On the other hand, eight other alleles found on the smaller frequencies. Two similar allele combinations were also found on DNA profiles of Celagi clan, which is also belong to the similar family, Pasek Catur Sanak Bali Mula. The two allele are haplotype 6 and 5 found in both, Pasek Kayuan and Pasek Celagi. The haplotype 6 as dominant allele of Celagi clan by adoption, haplotype 5 however, the frequency was the lowest. This allele only detected in one member of each clan due to mutation.